2021
DOI: 10.1021/acsanm.1c01007
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretically-Deposited CdSe Quantum Dot Films for Electrochromic Displays and Smart Windows

Abstract: Electrophoretically deposited (EPD) quantum dots (QDs) can be charged electrochemically via electron injection from a conducting substrate, leading to pronounced changes in their electrical and optical properties. The 180–550 nm thick EPD films composed of CdSe QDs with different diameters (2.8–6.3 nm) demonstrate a strong and reversible electrochromic response due to bleaching of excitonic transitions. The number of injected electrons was found to increase with QD size from 1.3 (QD diameter of 2.8 nm) to 6 (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…This estimated range of electrons injected per QD is consistent with the estimates of Houtepen and coworkers for low coverage QD films, and more recently, the electrochromic studies of Aniskevich et al, but lower than studies by Houtepen and coworkers for multilayer QD films where five electrons or more appear to be injected per QD, limited by void size in the QD film . Other studies have reported that up to 50–150 electrons per QD can be injected by either chemical or electrochemical reduction in the solution. ,,,, If 50–150 electrons per QD were transferred during voltammetric reduction, however, due to charge injection into surface traps or injection leading to absorbance bleaching, the Faradaic peak currents and the charge density in Figure S8 would have been correspondingly 50–150× larger.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…This estimated range of electrons injected per QD is consistent with the estimates of Houtepen and coworkers for low coverage QD films, and more recently, the electrochromic studies of Aniskevich et al, but lower than studies by Houtepen and coworkers for multilayer QD films where five electrons or more appear to be injected per QD, limited by void size in the QD film . Other studies have reported that up to 50–150 electrons per QD can be injected by either chemical or electrochemical reduction in the solution. ,,,, If 50–150 electrons per QD were transferred during voltammetric reduction, however, due to charge injection into surface traps or injection leading to absorbance bleaching, the Faradaic peak currents and the charge density in Figure S8 would have been correspondingly 50–150× larger.…”
Section: Resultssupporting
confidence: 88%
“…200 meV of the difference in E CB between the two measurement approaches arises from the stabilization of the one-electron reduced state of the CdSe QD film by the Li + counter ion (see Figure and associated discussion below); and (ii) the remaining difference is attributed to stabilization of the reduced CdSe QD by the near-surface environment, specifically the ODiPA/ITO interfacial region (see discussion in the text). In addition, plotted in (A) and (B) are E CB estimates obtained from spectroelectrochemical studies of adsorbed or electrophoretically deposited monolayer/multilayers of CdSe QDs (Spittel et alref ; Aniskevich et alref ) and CdSe QD solutions (Ashokan and Mulvaneyref ), demonstrating the range over which estimated E CB values can vary.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations